18F‐Fluorodeoxyglucose–Positron Emission Tomography As an Imaging Biomarker in a Prospective, Longitudinal Cohort of Patients With Large Vessel Vasculitis. Issue 3 (6th February 2018) - Grayson, Peter C.; Alehashemi, Sara; Bagheri, Armin A.; Civelek, Ali Cahid; Cupps, Thomas R.; Kaplan, Mariana J.; Malayeri, Ashkan A.; Merkel, Peter A.; Novakovich, Elaine; Bluemke, David A.; Ahlman, Mark A.
Abstract : Objective: To assess the clinical value of 18 F‐fluorodeoxyglucose (FDG) positron emission tomography (PET) in a prospective cohort of patients with large vessel vasculitis (LVV) and comparator subjects. Methods: Patients with Takayasu arteritis and giant cell arteritis were studied, along with a comparator group consisting of patients with hyperlipidemia, patients with diseases that mimic LVV, and healthy controls. Participants underwent clinical evaluation and FDG‐PET imaging, and patients with LVV underwent serial imaging at 6‐month intervals. We calculated sensitivity and specificity of FDG‐PET interpretation for distinguishing patients with clinically active LVV from comparator subjects and from patients with disease in clinical remission. A qualitative summary score based on global arterial FDG uptake, the PET Vascular Activity Score (PETVAS), was used to study associations between activity on PET scan and clinical characteristics and to predict relapse. Results: A total of 170 FDG‐PET scans were performed in 115 participants (56 patients with LVV and 59 comparator subjects). FDG‐PET distinguished patients with clinically active LVV from comparator subjects with a sensitivity of 85% (95% confidence interval [95% CI] 69, 94) and a specificity of 83% (95% CI 71, 91). FDG‐PET scans were interpreted as active vasculitis in most patients with LVV in clinical remission (41 of 71 [58%]). Clinical disease activity status, disease duration, body mass index, and glucocorticoid use were independently associated with activity on PET scan. Among patients who underwent PET during clinical remission, future clinical relapse was more common in patients with a high PETVAS than in those with a low PETVAS (55% versus 11%; P = 0.03) over a median follow‐up period of 15 months. Conclusion: FDG‐PET provides information about vascular inflammation that is complementary to, and distinct from, clinical assessment in LVV. FDG‐PET scan activity during clinical remission was associated with future clinical relapse.